Impact of inequality-related media coverage on the concerns of the citizens - Matthias Diermeier; Henry Goecke; Judith Niehues; Tobias Thomas (EcoAustria - Institute for Economic Research, 2017)
Income distribution and inequality play a central role in the public and political debate in many developed and democratic countries. An increasing literature on (mis)perception of the distribution of income reveals that people have very little knowledge about the degree of inequality in the society and its development over time. The jury is still out on what actually drives the perception of inequality and related fairness evaluations. In this paper, we use data on the intensity of media coverage on inequality-related topics on a daily basis and match it with daily varying survey responses with respect to the concerns about the economic situation as well as the perceived fairness within the society. Our regression results suggest that first, cumulated media coverage on inequality during the last couple of days before an interview has a significant negative impact on the concerns about the economic situation of the society and second, that media coverage on inequality has a significant negative effect on the perception of social fairness. The effects remain significant when using varying definitions of inequality related media coverage and different estimation methods. Taking all results into account, our paper provides evidence that media coverage is well likely to form perception at the individual level - detached from real world developments.
Keywords: D63; D84; H23; 330; Inequality; inequality perception; media bias